Electric Vehicle Technology Course for Generation Z: Discussion-Based, Project-Based, and Laboratory Activities - Imawati, Iftitah; Mubarok, Husein; Wahyuni, Elvira Sukma (Department of Physics Education, Universitas Mataram, 2024)
Generation Z, growing up in an era of constantly evolving technology and information, presents new challenges for the world of education. They are known as a digitally connected generation, quick to adapt to technological advancements, and in search of interactive experiences in learning. One excellent step in responding to these needs is using suitable learning methods. For the new mandatory course, Electric Vehicle Technology with a weight of 3 credits, in the Electrical Engineering Bachelor's Program at Universitas Islam Indonesia, a learning approach that matches the characteristics and preferences of Generation Z was used. In the odd semester of 2023/2024, two classes were opened for Electric Vehicle Technology, class A with 56 students and class B with 50 students. The combination of discussion-based learning methods, project-based learning, and laboratory activities was used in the learning process to meet the needs of Generation Z students in the Electric Vehicle Technology course. The assessment used consisted of summative and formative assessments. The scoring rubric was key in helping to categorize the value of the work done by students. The integration of assessment weights considers the contribution from each learning model. Overall, the application of discussion-based learning models, project-based learning, and laboratory activities together have created a stimulating learning environment and aroused student enthusiasm in the Electric Vehicle Technology course. With combined methods of learning, the course passing rate for each of the course's learning outcomes was higher than 80%. For class A, the overall course passing rate was 88%, while for class B, it was 84%.